Physical activity and health in Chinese children and adolescents: expert consensus statement (2020) - Chen, Peijie (Br J Sports Med, 2020)
China is experiencing significant public health challenges related to social and demographic transitions and lifestyle transformations following unprecedented economic reforms four decades ago. Of particular public health concern is the fourfold increase in overweight and obesity rates in the nation’s youth population, coupled with the low prevalence of adolescents meeting recommended levels of physical activity. Improving the overall health of China’s more than 170 million children and adolescents has become a national priority. However, advancing nationwide health initiatives and physical activity promotion in this population has been hampered by the lack of a population-specific and culturally relevant consensus on recommendations for achieving these ends. To address this deficiency and inform policies to achieve Healthy China 2030 goals, a panel of Chinese experts, complemented by international professionals, developed this consensus statement. The consensus was achieved through an iterative process that began with a literature search from electronic databases; in-depth reviews, conducted by a steering committee, of the resulting articles; and panel group evaluations and discussions in the form of email correspondence, conference calls and written communications. Ultimately, the panel agreed on 10 major themes with strong scientific evidence that, in children and adolescents aged 6–17, participating in moderate to vigorous physical activities led to multiple positive health outcomes. Our consensus statement also (1) highlights major challenges in promoting physical activity, (2) identifies future research that addresses current knowledge gaps, and (3) provides recommendations for teachers, education experts, parents and policymakers for promoting physical activity among Chinese school-aged children and adolescents. This consensus statement aligns with international efforts to develop global physical activity guidelines to promote physical activity and health and prevent lifestyle-related diseases in children and adolescents. More importantly, it provides a foundation for developing culturally appropriate and effective physical activity interventions, health promotion strategies and policy initiatives to improve the health of Chinese children and adolescents.